Performance test of a small-scale turbojet engine running on a palm oil biodiesel - jet a blend - Gires, Ezanee; Abu Talib, Abd. Rahim; Ahmad, Mohamed Tarmizi; Idris, Azni (2012)
The performance characteristics of an Armfield CM4 turbojet engine are investigated by running it on conventional kerosene fuel Jet A and on palm oil biodiesel fatty acid methyl ester (PME) 20% volumetric blend with Jet A. Values of thrust, fuel flow, temperature and pressure distribution along the engine and rpm are available from experimental measurements, whereas other values of merit are calculated using parametric cycle analysis and one dimensional flow assumptions. Heating values of each fuel mixture are obtained and used to estimate changes in CM4 performance which are verified experimentally. It was found that the 20% PME blend with Jet A produced comparable results compared to the benchmark tests, particularly with thrust and thermal efficiency. Slight performance penalties occurred due to the lower energy content of the biodiesel blend. The efficiency of the combustor improved with the addition of biodiesel while the other component efficiencies remained collectively consistent.